Efforts to Increase Knowledge of Non-Communicable Diseases in the Bagongan District, Kulon Progo, Yogyakarta Special Region - Muhammad Aris Wafdulloh; Dyah Maharani Puspita Sari; Faradhita Afira Octa Priheningtyas; Muthmainnah Galuh Setia Hadi; Almer Ramadhani; Ghea Alya Mevia; Gadis Brillian; Rhestra Ahnaf Fawwaz; Arya Adiningrat (Jurnal Pengabdian Masyarakat Bestari, 2023)
Counseling campaigns on non-communicable diseases are a promotion strategy for health problems such as hypertension and diabetes mellitus. The disease is the third highest leading cause of death in Indonesia. This counseling is expected to be the first step in avoiding the dangers of non-communicable diseases. Counseling is conducted by lecture, discussion and question and answer methods. The number of counseling audience was twenty participants. Evaluation of counseling results is conducted through pre-test and post-test using questionnaires. Evaluation of counseling results showed that the average total score of public knowledge about non-communicable diseases had increased significantly. Analysis of the comparison test with Wilcoxon's formula showed an increase in knowledge of 30.5%. Based on the results of the evaluation of community service activities, it can be concluded that counseling with dissemination, question and answer methods could be effective in increasing public knowledge about non-communicable diseases.